Ancient Patrilineal Lines and Relatively High ECAY Diversity Preserved in Indigenous Horses Revealed With Novel Y-Chromosome Markers - Liu, Shuqin; Yang, Yunzhou; Pan, Qingjie; Sun, Yujiang; Ma, Hongying; Liu, Yu; Wang, Min; Zhao, Chunjiang; Wu, Changxin (Frontiers in Genetics, 2020)
Extremely low nucleotide diversity of modern horseY-chromosome has been reported,and only poor phylogenetic resolution could be resulted from limited Y-chromosome markers. In this study, three types of horse Y-chromosome markers, including SNPs, CNVs, and allele-specific CNVs, were developed by screening more than 300 male horses from 23 indigenous Chinese horse populations and 4 imported horse breeds. Fourteen segregating sites including a novel SNP in the AMELY genewere found inapproximately 53kb of male-specific Y-chromosome sequences. CNVs were detected at 11 of 14 sites, while allele-specific CNVs at 6 polymorphic sites in repeated fragments were also determined. The phylogenetic analyses with the SNPs identified in this study and previously published 51 SNPs obtained mainly from European horses showed that indigenous Chinese horses exhibit much deeper divergence than European and Middle Eastern horses, while individuals of Chinese horses with the C allele of the AMELY gene constituted the most ancient group. ViaSNPs, CNVs andallele-specific CNVs, much higher diversity of paternal lines can be detected than those identified with merely SNPs. Our results indicated that there are ancient paternal horse lines preserved in southwestern China, which sheds new light on the domestication and immigration of horses, and suggest that the priorities of the conservation should be given to the ancient and rare paternal lines. These three marker types provided finer phylogenetic resolution of horse patrilineal lines, and the strategies used in the present study also provide valuable reference for the genetic studies of other mammalian patrilineages.